2014
DOI: 10.1164/rccm.201310-1776oc
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Th1 and Th17 Cells in Murine Models of Malignant Pleural Effusion

Abstract: In mouse models of MPE, IFN-γ inhibited Th17-cell differentiation, whereas IL-17 inhibited Th1-cell differentiation. IL-17 inhibited the formation of MPE and improved the survival of mice bearing MPE; in contrast, IFN-γ promoted MPE formation and mouse death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 39 publications
2
60
1
Order By: Relevance
“…These data indicate that both endogenous and exogenous IL-17 are capable of inhibiting the development of MPE. As reported in our previous paper (Lin et al, 2014), expressions of both CD34 and Ki-67 in pleural tumors are increased in IL-17 / mice. We extended these work and further observed that intraperitoneal injection of anti-IL-17 mAb in WT mice significantly increased the numbers of both CD34 + ( Figure 2A) and Ki-67 + cells (P<0.01) ( Figure 2B); while intraperitoneal injection of rmIL17 in IL-17 …”
Section: Il-17 Inhibited Mpe Formationsupporting
confidence: 84%
See 4 more Smart Citations
“…These data indicate that both endogenous and exogenous IL-17 are capable of inhibiting the development of MPE. As reported in our previous paper (Lin et al, 2014), expressions of both CD34 and Ki-67 in pleural tumors are increased in IL-17 / mice. We extended these work and further observed that intraperitoneal injection of anti-IL-17 mAb in WT mice significantly increased the numbers of both CD34 + ( Figure 2A) and Ki-67 + cells (P<0.01) ( Figure 2B); while intraperitoneal injection of rmIL17 in IL-17 …”
Section: Il-17 Inhibited Mpe Formationsupporting
confidence: 84%
“…In the previous study (Lin et al, 2014), we have demonstrated that more pleural tumor foci and bloody MPE are found in IL-17 / mice as compared with WT mice 14 days after intrapleural injection of LLC cells. Here once again we confirmed that radiotracer uptake was significantly increased on FDG-PET scanning in IL-17 / mice ( Figure 1A).…”
Section: Il-17 Inhibited Mpe Formationmentioning
confidence: 81%
See 3 more Smart Citations